Biofilm Formation of Probiotic Saccharomyces cerevisiae var. boulardii on Glass Surface during Beer Bottle Ageing - Khosrow Mohammadi; Per Erik Joakim Saris (Beverages, 2022)
While brewing probiotic beer using Saccharomyces cerevisiae var. boulardii, we noticed the yeast potentially makes biofilm in glass bottles as the bottles get hazy. In this study, S. cerevisiae var. boulardii CNCM I-745 was used as a starter culture to produce probiotic beer. We studied the biofilm parameters combined with FLO11 mRNA expression and used light and scanning electron microscopy to document biofilm formation and structure. Our results revealed that ageing the beer and maturing from a sugar-rich to a sugar-limited beer, along with the stress factors from the brewing process (pH reduction and produced metabolites), led to an increase in biofilm mass; however, the viable count remained relatively stable (approximately 7.1 log10 cells/mL). Biofilm S. boulardii cells showed significantly higher FLO11 mRNA expression in the exponential and stationary phase compared to the planktonic cells. This study, therefore, provides evidence that S. cerevisiae var. boulardii makes biofilm on glass surfaces during beer bottle ageing. The impact of complications caused by formed biofilms on returnable bottles emphasizes the significance of this study.